2011
DOI: 10.1590/s1415-47572011005000032
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of beta-thalassemia mutations in patients from the state of Rio Grande do Norte, Brazil

Abstract: 35 unrelated individuals were studied for characterization as either heterozygous or homozygous for beta-thalassemia. Molecular analysis was done by PCR/RFLP to detect the mutations most commonly associated with beta-thalassemia (β0IVS-I-1, β+IVS-I-6, and β039). In the patients who showed none of these mutations, the beta-globin genes were sequenced. Of the 31 heterozygous patients, 13 (41.9%) had the β+IVS-I-6 mutation, 15 (48.4%) the β0IVS-I-1 mutation, 2 (6.5%) the β+IVS-I-110 mutation and 1 (3.2%) the β+IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…The β-thal prevalence in North and Northeast Brazil is still undetermined and the few studies from this region to report molecular aspects showed a higher prevalence of HBB: c.92þ6T>C and HBB: c.92þ1G>A. However, the HBB: c.92þ5G>C [IVS-I-5 (G>C); β nt 147 (G>C)], an Indian-Asian mutation mostly described on the Indian subcontinent, Pakistan, Sri Lanka, Mauritius Island, Oman and other part of the Middle East, has also been found (13)(14)(15).…”
mentioning
confidence: 99%
“…The β-thal prevalence in North and Northeast Brazil is still undetermined and the few studies from this region to report molecular aspects showed a higher prevalence of HBB: c.92þ6T>C and HBB: c.92þ1G>A. However, the HBB: c.92þ5G>C [IVS-I-5 (G>C); β nt 147 (G>C)], an Indian-Asian mutation mostly described on the Indian subcontinent, Pakistan, Sri Lanka, Mauritius Island, Oman and other part of the Middle East, has also been found (13)(14)(15).…”
mentioning
confidence: 99%
“…Different from the other states in our study, the most common mutation in the state of Pernambuco was IVS-I-5 (G>C). This mutation is very common in Asia, especially in Malaysia and Indonesia and in several regions of India [29]. In studies conducted by Khan et al from 2011–2013 in four provinces of Pakistan, the most frequent mutation detected in a total of 63 samples of β-thalassemia was IVS-I-5(G>C) (33.9%)[30].…”
Section: Discussionmentioning
confidence: 99%
“…Hematological and biochemical studies by others of other populations with similar or different mutation patterns showed significant changes in these characteristics between different mutations. In a Brazilian population where IVS-I-110, IVS-I-6 and IVS-I-1 are predominant mutations [31,32], Bertuzzo et al [33] showed that IVS-I-1 was the relatively severe mutation and IVS-I-6 was the mildest one, while IVS1-110 was intermediate in severity. In a Pakistani study, Khattak et al [34] reported a frame shift mutation, FR 8-9, to have the lowest hematological RBC parameters.…”
Section: Discussionmentioning
confidence: 99%